Strategi Campaign Melalui Seni Campursari â€œSiswo Laras Budoyoâ€ sebagai Upaya Mengembangkan Kepedulian Masyarakat bagi Pendidikan Khusus di Kabupaten Bojonegoro - Sutras, Sutras (Jurusan Pendidikan Luar Biasa)
AbstractPublic awareness of the importance of education must continue to be increased including education care for Children with Special Needs. The negative public perception of the ability of Children with Special Needs must also be changed to a positive perception so that children with special needs have the opportunity to improve their competence.The purpose of research